Ibu dan Karir:Kajian Fenomenologi terhadap Dual-Career Family - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRAK This phenomenology qualitative research was conducted in order to know the meaning of 'career' for working woman. This research attempted to see the meaning of 'career' from woman's or mother's point of view as the individual with the attributes as a mother. Mother in dual-career family obviously has double roles